KONSEP ALTERNATIF PENYELESAIAN SENGKETA DAN APLIKASINYA DALAM HUKUM KELUARGA - Salam, Nor (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This study is methodologically a descriptive study that focuses on tracking the basic concepts of alternative dispute resolution as well as their application in the context of family law (fiqh al-usrah). The conclusions of this study show that even historically, the birth of the concept of alternative dispute resolution is more related to the business world which requires patterns of dispute resolution quickly and efficiently. However, legal dispute resolution patterns based on this model can also be applied in the field of fiqh al-usrah. In fact, dispute resolution through such a process is in line with the moral ideal of the Quran which requires that any dispute resolution must be built on the principle of al-ishlah, including in the context of family law.